Crop raiding by wildlife on subsistence homesteads around the Hluhluwe game reserve South Africa - Raphela, Tlou Daisy (My University, 2019)
The literature on human-wildlife conflict shows that subsistence farming is a neglected area of research in South Africa. Instead the focus has been on the interaction between wildlife and commercial farmers, in particular livestock losses because of carnivore attacks. Studies of crop losses to wildlife in subsistence farming are lacking. The aim of my study was therefore to investigate the impact of crop raiding by wildlife, particularly rodents and primates, on subsistence farmers on the edge of the Hluhluwe Game Reserve, in the northern KwaZulu-Natal Province, South Africa. The main hypothesis was that crop raiding by wildlife would impact the livelihood and lives of subsistence farmers and compromise their food security. I first investigated the seasonal variation in crop raiding behaviour by measuring the level of damage, identifying the crop raiding animal groups and the crop types frequently raided. The highest level of crop damage was during the dry season, caused by rodents, birds and insects. Maize (Zea mays) suffered the highest level of damage. Interestingly, primates in the Hluhluwe Game Reserve never transgressed the farm boundaries to raid crops, but were observed feeding more than travelling next to the farms. I next investigated the nutritional and economic impact of crop raiding on subsistence farmers seasonally. Again, the highest nutritional and economic impact of crop raiding was during the dry season and the highest nutritional loss was recorded for maize overall; the annual potential income loss was about R2 427/annum (about US$180.71). Next, I investigated the opinions and perceptions of subsistence farmers on crop raiding and the control measures employed by farmers to deter crop-raiding animals. Farmers differed in their opinions and perceptions to crop raiding in relation to their proximity to the reserve boundary; farmers closer to the reserve viewed wildlife as pests more than farmers further away from the reserve. Several candidate crop raiders were identified, and there were positive correlations between the levels of control measures employed by farmers and factors known to influence crop raiding by wildlife (i.e. distance of farms from the reserve, crop raiding animals and crop types raided). Subsequently, I investigated the opinions and perceptions of conservation practitioners on crop raiding and issues related to crop raiding by wildlife of surrounding subsistence farmers. I also assessed the implementation of community outreach programmes by the Hluhluwe Game Reserve management. Conservationists produced mixed responses and contradictions when asked about which animals: i) raided crops on adjacent farms; ii) were reported to raid crops by the neighbouring communities; and iii) escaped from the reserve. Overall, most conservationists reported that the reserve had not implemented community outreach programmes. By combining data from previous chapters, I assessed the effects of crop raiding on food security of subsistence homesteads; homestead dietary diversity was used as a proxy for food security. I found indicators of crop raiding by wildlife impacting the food security of these homesteads, particularly on small farms and larger homesteads. My study revealed that subsistence farmers are affected by wildlife but not to the extent anticipated. Some but not all the usual wildlife raiders were identified by this study. Farmers responded to crop raiding by using specific deterrents. Crop raiding appears to influence food security of the farmers, but its actual impact requires further study
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy 2019